2016
DOI: 10.17265/2328-7136/2016.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Disparities between Explanatory Models of Health Clients, Healthcare Providers and Health Insurer

Abstract: Abstract:We present qualitative data from a study in Ghana (2011), where the National Health Insurance Scheme (NHIS) was introduced to improve access to health care. In 2011 membership enrolment and retention in the scheme was stalling. To obtain better insights into socio-cultural factors that influence utilization of healthcare services and the NHIS this study compared Explanatory Models of healthcare clients with those of primary healthcare providers and the NHIS regarding illness, the need for, the quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The intervention design was based on the premise that involving clients in planning, provision and monitoring of healthcare and health insurance services is an important ingredient for increased healthcare utilization and health insurance enrolment because engagement ensures better understanding of the service delivery processes, builds risk awareness among clients and improves service quality [14,25]. Moreover, a qualitative study conducted at the start of the project with clients, providers and insurers revealed that perceptions on what constitutes good quality services differ among these three actors [26]. Improved mutual understanding would enable providers and insurers to address non-technical quality concerns as perceived by clients.…”
Section: Design and Implementation Of The Community Engagement Intervmentioning
confidence: 99%
See 1 more Smart Citation
“…The intervention design was based on the premise that involving clients in planning, provision and monitoring of healthcare and health insurance services is an important ingredient for increased healthcare utilization and health insurance enrolment because engagement ensures better understanding of the service delivery processes, builds risk awareness among clients and improves service quality [14,25]. Moreover, a qualitative study conducted at the start of the project with clients, providers and insurers revealed that perceptions on what constitutes good quality services differ among these three actors [26]. Improved mutual understanding would enable providers and insurers to address non-technical quality concerns as perceived by clients.…”
Section: Design and Implementation Of The Community Engagement Intervmentioning
confidence: 99%
“…Community Engagement uses existing community groups or associations in assessing healthcare providers and the NHIS district offices to identify service quality gaps. The assessment employed elements of the MyCare tool [26]. The MyCare tool is an instrument used to elicit clients' perception of service quality.…”
Section: Design and Implementation Of The Community Engagement Intervmentioning
confidence: 99%